Clays and Clay Minerals, Vol. 54, No. 3, 275-294, 2006. - Laverret, Emmanuel; Mas, Patricia Patrier; Beaufort, Daniel; Kister, Philippe; Quirt, David; Bruneton, Patrice; Clauer, Norbert (The Clay Minerals Society, 2006)
Unconformity-related uranium deposits, which represent a significant high-grade uranium resource, are systematically surrounded by a host-rock alteration halo enriched in clay minerals. Illite is often the major clay mineral component of the halo and it displays a variable crystal structure. New data are provided on the crystal structure and the chemistry of illite encountered within and outside of the alteration halo surrounding the Shea Creek deposit. Two illite populations were distinguished using textural and structural criteria: samples rich in the tv-1M polytype display thin (sub-micrometer) and `hairy' shapes, while samples richer in the cv-1M polytype contain illites with rigid lath-like shapes several micrometers wide. In barren `regional' sandstone, the trends with depth of the textural and microstructural properties of illite particles are: (1) an increase of particle size, (2) an evolution to a more isometric form, and (3) a dominance of the cv-1M polytype over the tv-1M polytype. These trends record diagenetic processes under conditions of deep burial and differ from those observed in altered sandstone around the uranium mineralization. The altered sandstone is characterized by enrichment in the tv-1M polytype near the unconformity and/or brittle structural features. This tv-1M illitization took place in response to structurally-controlled infiltration of basement rocks by diagenetic brines which were further recycled after interaction into the overlying basin. Variations of the illite structural and textural properties may result from nucleation/growth kinetics and may be indicative of a change in the flow regime, and/or a change of saturation state of the fluid vs. illite. The tv-1M illite may be favored in environments characterized by a high fluid/rock ratio and a high supersaturation state of the fluids in proximity to mineralization.
Mineralogy and Geochemistry of the Host-rock Alterations Associated with the Shea Creek Unconformity-type Uranium Deposits (athabasca Basin, Saskatchewan, Canada). Part 1. Spatial Variation of Illite Properties
gsccm-54-3-01-lav.pdf 2.21MB PDF/A Document.
Keywords: Periodicals; Geology; Athabasca Basin; Crystal Chemistry; Crystal Form; Crystal Structure; Host-rock Alteration; Illite; Kaolin Minerals; Sudoite; Unconformity-type Uranium Deposit